Improving workplace safety: an ergonomic assessment and engineering control approach - Abdullah, M. D.; Ahmad, A. A.; Abdul Rahman, S. M. B. (Smart Manufacturing Research Institute (SMRI), 2025)
Workplace injuries in machining departments, particularly back pain from manual handling, reduce productivity and increase manpower shortages. This study aimed to identify the root causes of these injuries and propose an engineering control solution through the Plan-Do-Check-Act (PDCA) cycle. Hazard Identification, Risk Assessment, and Risk Control (HIRARC), Ishikawa diagram analysis, and ergonomic assessment using the Rapid Entire Body Assessment (REBA) were applied to evaluate existing practices. The findings showed that lifting cutting tools from low storage racks produced a high REBA score of 9, indicating a high risk of musculoskeletal disorders. A new ergonomically designed storage rack concept was developed and evaluated using CATIA V5 software, with three alternatives compared through a Pugh Chart. Design B, which eliminated the need for trunk bending, was selected. Reassessment revealed that the REBA score decreased from 9 to 2, while the risk score for back pain was reduced from 12 to 3, achieving a 75% risk reduction. These improvements demonstrate a significant enhancement in workplace safety, reducing injury risks and improving productivity. The study highlights how ergonomic interventions integrated with the PDCA framework can provide practical solutions for minimising occupational hazards and ensuring sustainable productivity.